PENERAPAN METODE DATA MINING (NAÏVE BAYES) UNTUK MENGANALISIS TINGKAT MUTU PELAYANAN (TMP) PADA PELANGGAN STUDY KASUS PT PLN BATAM - Rika Harman (Universitas Putera Batam, 2013)
PT PLN Batam as Pemegang Izin Usaha Ketenagalistrikan Untuk Umum (PIUKU) with a working area of ​​Batam, Rempang and Galang, always committed to providing the best service to customers by continuing to provide electricity and keandalanya an ongoing effort by PT PLN Batam. This paper aims to conduct an analysis of the quality of services, which is expected to facilitate the operations of customer service by PT PLN Batam especially the service. Tool or measuring devices used is data mining by applying Naive Bayes. Results are expected later dimensions of customer satisfaction is fulfilled by the management of PT PLN Batam especially in the customer service, the customer service process is expected to take place either because any customer complaints can be managed as well as quickly and accurately anticipated. When viewed from the standpoint of management, to do a study or a special study of the trends-trends that occur on existing customer data. So that the management is always ready with the turmoil. The ultimate goal will change towards the better of the management of PT PLN Batam in the service process.